2002
DOI: 10.1038/sj.onc.1205800
|View full text |Cite
|
Sign up to set email alerts
|

Selective clonal expansion and microenvironmental permissiveness in tobacco carcinogenesis

Abstract: Historically our knowledge about the direct carcinogenic activity of cigarette smoke and its constituents grew from painting experiments on the skin of mice to produce papillomas and carcinomas. The neutral fraction of cigarette smoke condensate had most of the carcinogenic activity in this test and was rich in carcinogenic polycyclic aromatic hydrocarbons (PAHs), the most abundant by far being BP. However, the concentration of BP in the condensate was only about 2% the amount of pure BP required to cause skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 136 publications
1
33
0
Order By: Relevance
“…This observation is significant considering that cigarette smoke contributes more to the promoting than the initiating phase of cancer. 11 Our results do not explain the entire carcinogenic nature of the complex mixtures found in cigarette smoke, however, these in vitro studies do indicate that a much overlooked class of compounds found in cigarette smoke that can induce molecular events consistent with the tumor promoting phase of cancer.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This observation is significant considering that cigarette smoke contributes more to the promoting than the initiating phase of cancer. 11 Our results do not explain the entire carcinogenic nature of the complex mixtures found in cigarette smoke, however, these in vitro studies do indicate that a much overlooked class of compounds found in cigarette smoke that can induce molecular events consistent with the tumor promoting phase of cancer.…”
Section: Discussionmentioning
confidence: 53%
“…DH, the heat-inactivated control. (BaP), 46 and that cigarette smoke is a strong promoter and weak complete carcinogen 11,[47][48][49] suggest that this fraction could significantly contribute to cancer. Ten to 15 years after giving up smoking, the exsmoker faces the same low risk of developing cancer of the upper digestive tract, the lung, the pancreas, and the urinary tract as the nonsmoker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may think that the decreased cell growth may prevent breast carcinogenesis after cigarette smoking. However, consistent with the selective 'clonal' expansion and microenvironment permissiveness in tobacco-mediated lung carcinogenesis (Rubin, 2002), a single transformed normal breast epithelial cell can give rise to a tumor. Thus, the main focus of our study was to examine the underlying mechanisms involved in the transformation of normal breast epithelial cells by CSC.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke is primarily considered to be a tumor-promoting and co-carcinogenic agent and only a weak complete carcinogen [4][5][6]. Cigarette smoke or its components cause DNA mutations and chromosomal damage, protein modifications, and expression changes of genes involved in cell death, inflammation, DNA repair and cell cycle regulation [4,[7][8][9][10][11]. In addition, the molecular response to cigarette smoke exposure is cell-and tissue-specific and varies with the type of exposed target organ and tobacco product [7,12,13].…”
Section: Introductionmentioning
confidence: 99%